Lessons From Mass-Testing for Coronavirus Disease 2019 in Long-Term Care Facilities for the Elderly in San Francisco. (20th July 2020) - Louie, Janice K; Scott, Hyman M; DuBois, Amie; Sturtz, Natalya; Lu, Wendy; Stoltey, Juliet; Masinde, Godfred; Cohen, Stephanie; Sachdev, Darpun; Philip, Susan; Bobba, Naveena; Aragon, Tomas; et al.
Abstract: Coronavirus disease 2019 can cause significant mortality in the elderly in long-term care facilities (LTCF). We describe 4 LTCF outbreaks where mass testing identified a high proportion of asymptomatic infections (4%–41% in healthcare workers and 20%–75% in residents), indicating that symptom-based screening alone is insufficient for monitoring for COVID-19 transmission.